High strain rate bond characteristics of reinforced concrete beam-ends. (August 2019) - Jacques, Eric; Saatcioglu, Murat
Highlights: Strain rates consistent with far range explosive detonation were achieved. High strain rates enhanced static bond strength of beam-ends in the range of 30–50%. Strain rate effects promoted dynamic rebar fracture over static bond failures. The shape of bond-slip curves was not significantly influenced by high strain rates. Beam-end tests were well suited for comparative low and high strain rate tests. Abstract: Flexural beam-end tests were conducted to characterize the effect of high strain rates on reinforcement bond in concrete. A total of 14 flexural beam-end bond specimens, constructed with 20 M deformed reinforcement embedded in 50 MPa concrete, were tested. The beam-ends were subjected to static and dynamic testing generating strain rates of 5.0 × 10 −6  s −1 and 1.2 s −1, respectively. Half of the beam-ends were constructed with lengths of bonded reinforcement of 200 mm, with the remainder having a longer bond length of 400 mm. The bond stress-slip response of the specimens was constructed using elastic strain measurements obtained from the bonded region. High strain rates were found to significantly enhance the bond strength of the beam-ends, whereas they did not significantly influence the general shape of the bond stress-slip curves. Bond strength obtained under rapid loading conditions exhibited approximately the same strain rate sensitivity as has been observed by others in the literature for similar high strain rate tests. Flexural beam-end tests were found to be well suited for high strain rate testing, and are recommended for future studies, provided a safe and convenient dynamic loading fixture can be employed.